Rehabilitation of resorbed mandibular ridges using mini implant retained overdentures: A case series with 3 year follow-up - Pooja Kumari; Mahesh Verma; Vikrant Sainia; Rekha Gupta; Shubhra Gill (Wolters Kluwer Medknow Publications, 2016)
With the increasing average life expectancy of human beings, the need to cater geriatric patients is ever increasing. Complete dentures are an indispensable tool in this regard. The loose and unstable lower complete denture owing to residual ridge resorption is one of the most common problems faced by edentulous patients. Dental implant retained overdentures have emerged as an efficient treatment modality for such patients. Though useful, not every patient is a suitable candidate to go for conventional implant-borne prosthesis, limitation being the available bone width. In such cases, mini implants may be used for augmenting the retention of the dentures and improving the quality of life of patients. In this case series, rehabilitation of three compromised cases with mini implant retained overdentures have been described wherein patients are experiencing instability of lower denture due to thin resorbed mandibular ridges. In one of the cases, three mini implants placed in A, C, and E position were splinted using a cemented bar to retain the mandibular denture. The other two cases were rehabilitated using unsplinted ball type one piece mini implants placed in A, C, and E position in one case and B and D position in another case. Though splinted bar design should be preferred but the lack of available vertical space precluded the utilization of bar in other two cases. The results were found to be satisfactory with no complications reported during a follow-up period of over 3 years in all the cases.